Safety culture in healthcare: mixed method study - Lorenzini, Elisiane; Oelke, Nelly D; Marck, Patricia B (Journal of health organization and management, 2021)
PurposeHealthcare providers’ perceptions of management's effectiveness in achieving safety culture improvements are low, and there is little information in the literature on the subject. Objective: The overall aim of this study was to examine the patient safety culture within an interprofessional team – physicians, nurses, nurse technicians, speech therapist, psychologist, social worker, administrative support – practicing in an advanced neurology and neurosurgery center in Southern Brazil.Design/methodology/approachThe authors applied the safety attitudes questionnaire (SAQ) in a mixed methods study, with a quan→QUAL sequential explanatory approach.FindingsIn the quantitative phase, the authors found a negative safety climate through the SAQ. In the qualitative phase, the approach enabled participants to identify specific safety problems. For that, participants proposed improvements that were directly and quickly implemented in the workplace during the study. The joint analysis of the quantitative and qualitative data inferred that the information and reflections of the focus group participants supported and validated the SAQ statistical analysis results. This integrated approach illustrated the importance of various safety culture aspects as a multifaceted phenomenon related to healthcare quality.Originality/valueThis study provides explanations for why management is associated negatively with safety climate in healthcare institutions. In addition, the study provides a novel contribution adding value to mixed methods research methodology.